2015
DOI: 10.1002/ls.1307
|View full text |Cite
|
Sign up to set email alerts
|

Tribological effects of Cu, Fe and Zn nano-particles, suspended in mineral and bio-based oils

Abstract: Many studies focus on nanoparticles as lubricity additives but overlook the fact that wear produces nanosized debris during the field use. In order to simulate the fine metal contaminants, which are the most widespread in various field applications, prefabricated Fe, Cu and Zn nanoparticles were used. Their 0.01–1% suspensions in vegetable and mineral oils with or without ZDDP and ashless AW package were tested on four‐ball AW under 150‐N load. Tribological effects of nanoparticles were not significant in form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…As GNPs loading increases, nanofillers agglomerate and create bigger and asymmetric particles, which prevent movement of fluid layers on each other; hence the viscosity increased for higher loadings (0.75 and 1.0 wt.%) of GNPs-NO nano-lubricants. e same behaviour was observed by other researchers with different liquids and nano additives [54][55][56][57]. Wang et al observed about 86% improvement in the viscosity of distilled water on incorporation of Al 2 O 3 [54].…”
Section: Effect Of Gnps Loading On Viscosity Of Neemsupporting
confidence: 83%
“…As GNPs loading increases, nanofillers agglomerate and create bigger and asymmetric particles, which prevent movement of fluid layers on each other; hence the viscosity increased for higher loadings (0.75 and 1.0 wt.%) of GNPs-NO nano-lubricants. e same behaviour was observed by other researchers with different liquids and nano additives [54][55][56][57]. Wang et al observed about 86% improvement in the viscosity of distilled water on incorporation of Al 2 O 3 [54].…”
Section: Effect Of Gnps Loading On Viscosity Of Neemsupporting
confidence: 83%
“…Static COF was measured using 100 Hz data collection rate for improved sensitivity. COF data at such high collection rate is strongly affected by surface roughness and debris particles [10,11]. Therefore, fluctuations of COF curve were smoothened by averaging every 15 data points to get a representative segment of initial 10 friction cycles, Fig.…”
Section: Tribological Testsmentioning
confidence: 99%
“…This would suggest engaging iron particles in formulating VOs as magnetorheological fluids for ASA; nonetheless, the oxidation catalytic effect of this particles can be a barrier, unless a powerful chelated metal deactivator is employed. At the moment, it is uncertain whether metallic particles significantly improve lubricity of VOs, because the tribological behaviour of fine Cu, Fe and Zn nano‐particles at 0.1–1% wt in inhibited rapeseed oil were reported by Asadauskas and co‐researchers to not only have effects on the performance of the lubricant, but can also have ambivalent impacts on additives effectiveness. All the same, there are surface protection powder additives in nanoscale, which are effective in VOs.…”
Section: Surface‐protective Agents and Vegetable Oilsmentioning
confidence: 99%